STRATEGI PEMBERDAYAAN INKLUSIF: INTEGRASI PELATIHAN BAHASA ISYARAT BAGI TENAGA KESEHATAN DAN PELATIHAN KEWIRAUSAHAAN UNTUK PEREMPUAN DISABILITAS - Dheska Arthyka Palifiana; Sitti Khadijah; Devillya Puspita Dewi; Dita Septian Anggraini; Mufliha Hasan (Jurnal LENTERA, 2026)
This Community Service (Pengabdian kepada Masyarakat - PkM) is motivated by two interrelated issues: (1) low communication accessibility in health services for individuals with hearing disabilities, and (2) limited economic opportunities for women with disabilities. The program aims to implement an inclusive empowerment strategy by integrating two main activities: a sign language introductory workshop for health workers and entrepreneurship training—covering packaging, marketing of catfish nuggets, and the production of mini sushi and pizza—for women with disabilities. The activities employed participatory and training-based methods, conducted through parallel and integrated workshops. The first workshop trained health workers in basic sign language and inclusive communication. The second workshop equipped women with disabilities with practical skills in producing and marketing simple culinary products. Program evaluation was carried out through participant observation, pre-test and post-test questionnaires on satisfaction and knowledge, as well as photo and video documentation. The PkM was implemented from August to September 2024.The results demonstrate success in two key areas: (1) For health workers, there was an increase in understanding and basic skills in sign language communication, along with heightened awareness of the importance of accessible health services. (2) For women with disabilities, participants were able to independently apply culinary production skills, showed increased motivation to pursue entrepreneurship, and reported greater self-confidence. This PkM program successfully demonstrated that an integrated empowerment approach—simultaneously targeting capacity building for service providers (health workers) and beneficiaries (women with disabilities)—is effective in creating sustainable impact. The model offers a practical framework for fostering inclusive health communication and economic participation